(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
In 2020-2023, 34 types of pests belonging to 1 class, 3 genera, and 14 families were identified during the study of harmful entomofauna of Haloxylon and other sand-retaining plants planted in the dry bottom of the Aral Sea. The dominant species of these harmful organisms are large and small hump-backed grasshoppers. Imitrin 20% sus.k. is one of the main chemical preparations belonging to different groups against the large saxophone locust. The insecticide was tested at rates of consumption of 2-3-year-old larvae - 0.05 l/ha and against 4-5-year-old larvae - 0.1 l/ha: after 3 hours - 89.2-87.4%, 24- after 95.1-94.0%, after 72 hours - 96.3-95.6% biological efficiency was obtained. From new drugs Comprodor 350 s.k. (0.08 l/ha.), Starin, 30% s.d.g. (0.170 kg/ha.), Alpac 100 EC em.k. (0.1 l/ha.) showed higher biological efficiency respectively. It was recommended to use the above-mentioned preparations in the production in the established norms and terms.